Pulp chamber temperature rise in light-cure bonding of brackets with and without primer, in intact versus restored teeth - Gabriela Cenci SCHMITZ; Fernanda de Souza HENKIN; Mauricio MEZOMO; Mariana MARQUEZAN; Gabriela BONACINA; Maximiliano Schünke GOMES; Eduardo Martinelli Santayana de LIMA (Dental Press Editora, 2023)
ABSTRACT Objective: To evaluate the pulp chamber temperature rise (PCTR) in light-cure bonding of brackets with and without primer, in intact and restored mandibular central incisors (M1), maxillary first premolars (Mx4), and mandibular third molars (M8). Material and Methods: Ninety human teeth were included: M1 (n=30), Mx4 (n=30), and M8 (n=30). Light-cure bonding of brackets was performed in intact (n=60) and restored (n=30) teeth, with primer (n=60) or without (n=30) primer. PCTR was defined as the difference between initial (T0) and peak temperatures (T1), recorded with a thermocouple during light-cure bonding. Differences on PCTR between bonding techniques (primer vs. no primer), teeth types (M1 vs. Mx4 vs. M8), and teeth condition (intact vs. restored) were estimated by ANCOVA, with α=5%. Results: PCTR was significantly higher with the use of primer (2.05 ± 0.08oC) than without primer (1.65 ± 0.14oC) (p=0.02), and in M1 (2.23 ± 0.22oC) compared to Mx4 (1.56 ± 0.14oC) (p<0.01). There was no difference in the PCTR in M8 (1.77 ± 0.28oC) compared to M1 or Mx4 (p>0.05), and no difference between intact (1.78 ± 0.14oC) and restored (1.92 ± 0.08oC) teeth (p=0.38). There was no influence of dentin enamel thickness in the PCTR (p=0.19). Conclusion: PCTR was higher in light-cure bonding of brackets with primer, especially in M1. Light-cure bonding seems less invasive without primer.